Kajian Komposisi, Transisi, dan Camera Movement dalam Trailer Film KKN di Desa Penari - Prasetyo, Martinus Eko; Ahmad, Asrullah (Institut Seni Indonesia Yogyakarta, 2024)
Study Of Composition, Transition And Camera Motion On The Film Trailer Of KKN In Desa Penari. Indonesia has been rocked by many quality horror films in the last five years, where there have been many horror films made by original Indonesian filmmakers that have caught the attention of the audience, one of which is the film called KKN DI DESA PENARI which has become the second highest-grossing film in Indonesia by successfully attracting nine million viewers in Indonesia. the big screen and has aired in the United States, and this is the second largest achievement after the Avengers-End Game film ever to be released in 2019 with 11 million viewers. Of course, the success of this film promotion cannot be separated from the activity of showing the KKN film trailer IN THE DANIER VILLAGE. The role of the trailer in a film's main work is very important, because the process and presentation of the film trailer must be able to briefly represent the overall essence of the film. The trailer must be packaged in an interesting and serious manner in its production, because of this the author aims to conduct a visual analysis of the trailer for this best-selling film in Indonesia entitled KKN DI DESA PENARI in terms of composition, transition, and camera movement studies. With qualitative descriptive research methods, it will enrich the writing analysis references more broadly and in depth. This research produces variations of visual creativity to be more colorful and interesting to increase audience interest in the visuals of film trailers. In horror movie trailers, this will be a special trick, how the composition, transition, and camera movement must accommodate interesting visuals for the audience, especially in movie trailers.